The Influence of Liquidity, Profitability, and Leverage on Stock Prices in 2021-2023 (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The goal of this research is to explore the relationship between stock prices, liquidity, profitability, and leverage. This study focuses on transportation and logistics companies that were registered in the Indonesia Stock Exchange from 2021 to 2023. A quantitative approach was taken, utilizing secondary data derived from the annual financial statements of companies that were active during this time frame. The sample comprised 45 data points, selected using a purposive sampling technique. The independent variables include leverage, measured with the Debt to Equity Ratio (DER), profitability, assessed through Return on Assets (ROA), and liquidity, evaluated via the Current Ratio (CR). The dependent variable for this research is the stock price. The findings from this partial analysis reveal that liquidity significantly and negatively impacts stock price, with a t-count of -2.264 and a significance level of 0.029. However, the correlation between stock price and profitability was found to be insignificant, indicated by a significance value of 0.071 and a t-count of -1.853. Similarly, leverage does not significantly affect stock price, as evidenced by a t-count of -0.657 and a significance level of 0.515. Nonetheless, when considered collectively, the three factors of leverage, profitability, and liquidity do influence stock prices. According to the coefficient of determination (R2) test, these three variables account for 13.9% of the volatility in stock prices, leaving the remaining 86.1% to be attributed to external factors not examined in this study.